A note on the bulk modulus of a binary elastic mixture - Kolev, Marin; Markov, Konstantin (Ann. Sofia Univ. Fac. Math. and Inf., 2000)
The Hashin-Shtrikman and Walpole bounds on the effective bulk modulus of a binary elastic mixture are revisited. A simple method of derivation is given as a generalization of the approach, recently proposed by one of the authors in the absorption and scalar conductivity problems for a two-phase medium.